Side‐Chain Engineering for Enhancing the Molecular Rigidity and Photovoltaic Performance of Noncovalently Fused‐Ring Electron Acceptors. (30th June 2021) - Zhang, Xin; Li, Congqi; Qin, Linqing; Chen, Hao; Yu, Jianwei; Wei, Yanan; Liu, Xingzheng; Zhang, Jianqi; Wei, Zhixiang; Gao, Feng; Peng, Qian; Huang, Hui
Abstract: Side‐chain engineering is an effective strategy to regulate the solubility and packing behavior of organic materials. Recently, a unique strategy, so‐called terminal side‐chain (T‐SC) engineering, has attracted much attention in the field of organic solar cells (OSCs), but there is a lack of deep understanding of the mechanism. Herein, a new noncovalently fused‐ring electron acceptor (NFREA) containing two T‐SCs (NoCA‐5 ) was designed and synthesized. Introduction of T‐SCs can enhance molecular rigidity and intermolecular π–π stacking, which is confirmed by the smaller Stokes shift value, lower reorganization free energy, and shorter π–π stacking distance in comparison to NoCA‐1 . Hence, the NoCA‐5 ‐based device exhibits a record power conversion efficiency (PCE) of 14.82 % in labs and a certified PCE of 14.5 %, resulting from a high electron mobility, a short charge‐extraction time, a small Urbach energy ( E u ), and a favorable phase separation. Abstract : A noncovalently fused‐ring electron acceptor (NFREA) NoCA‐5 containing two terminal side‐chains (T‐SCs) is reported. Introduction of T‐SCs can improve molecular rigidity, which is confirmed by the smaller Stokes shift value and lower reorganization free energy. Combining noncovalent conformational locks and T‐SC engineering, the NoCA‐5 ‐based device exhibits a record power conversion efficiency (PCE) of 14.82 % and a certified PCE of 14.5 %.